2020
DOI: 10.1016/j.heliyon.2020.e04375
|View full text |Cite
|
Sign up to set email alerts
|

Color for the perceptual organization of the pictorial plane: Victor Vasarely's legacy to Gestalt psychology

Abstract: Victor Vasarely's (1906–1997) important legacy to the study of human perception is brought to the forefront and discussed. A large part of his impressive work conveys the appearance of striking three-dimensional shapes and structures in a large-scale pictorial plane. Current perception science explains such effects by invoking brain mechanisms for the processing of monocular (2D) depth cues. Here in this study, we illustrate and explain local effects of 2D color and contrast cues on the perceptual organization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In particular, lighter images appear to be closer when they are on a dark background. Dresp‐Langley and Reeves 1 mention that configuration with the weakest tonal contrasts tend to produce weaker depth effects.…”
Section: Itten's Color Contrasts Investigated In Academic Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, lighter images appear to be closer when they are on a dark background. Dresp‐Langley and Reeves 1 mention that configuration with the weakest tonal contrasts tend to produce weaker depth effects.…”
Section: Itten's Color Contrasts Investigated In Academic Literaturementioning
confidence: 99%
“…Dresp‐Langley and Reeves 1 made experiments that showed red as being a color that, when used in a saturated form at the center of configurations, yields statistically higher probabilities for the perception of seeming to look nearer when compared to blue.…”
Section: Itten's Color Contrasts Investigated In Academic Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For describing the significance and meaning of color in art, there is the dictum of the Hungarian-French 20th century painter and graphic designer Victor Vasarely [25]: "Every form is a base for color, every color is the attribute of a form." Put differently, if we see visual art as composed of geometrical objects, then color can be viewed as a property of these objects.…”
Section: Color Symmetry and Color Symmetrymentioning
confidence: 99%
“…Previous work using human two-alternative forced choice decision has shown that local color variations in two-dimensional pattern displays may significantly influence perceived relative distances [44][45][46][47]. In the present study, we use shapes that display perfect geometrical vertical mirror symmetry, as described further below here in Section 2.1, where visual uncertainty about symmetry is introduced by systematic variations in color (hue) and or saturation of local shape elements, leading to lesser or greater amounts of visual information content.…”
Section: Introductionmentioning
confidence: 99%